2022
DOI: 10.1590/0001-3765202220210731
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activity of Lactiplantibacillus plantarum 6.2 extracted from cocoa fermentation and its supernatant on Gardnerella vaginalis

Abstract: Search for alternative methods for the treatment of bacterial vaginosis has been growing, and probiotics being among them. The most well-known probiotic microorganisms are lactobacilli, which are naturally present in the vaginal microenvironment. Cocoa fermentation is a source of lactic acid bacteria, with lactobacilli being the most prominent. The aim of this study was to evaluate the antagonistic activity of Lactiplantibacillus plantarum 6.2 a strain of lactobacilli isolated from cocoa fermentation, and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…Rocchetti et al found that the cell-free supernatant of L. plantarum also had similar immunomodulatory capacity compared with live bacteria [31]. RAMOS et al demonstrated that the cell-free supernatant of Lactiplantibacillus plantarum 6.2 excluded Gardnerella vaginalis from the adhesion site, and has good bactericidal effect like live bacteria [32]. Our study suggested that the antioxidant and anti-inflammatory capacity of the cell-free supernatant was lower than that of whole postbiotics at the same dose, but the biological activity of cell-free supernatants is still not negligible, especially in terms of anti-inflammatory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Rocchetti et al found that the cell-free supernatant of L. plantarum also had similar immunomodulatory capacity compared with live bacteria [31]. RAMOS et al demonstrated that the cell-free supernatant of Lactiplantibacillus plantarum 6.2 excluded Gardnerella vaginalis from the adhesion site, and has good bactericidal effect like live bacteria [32]. Our study suggested that the antioxidant and anti-inflammatory capacity of the cell-free supernatant was lower than that of whole postbiotics at the same dose, but the biological activity of cell-free supernatants is still not negligible, especially in terms of anti-inflammatory capacity.…”
Section: Discussionmentioning
confidence: 99%